International Committee on Systematics of Prokaryotes Subcommittee on the taxonomy of Mollicutes: Minutes of the closed meeting, 8 July 2018, Portsmouth, New Hampshire, USA. Issue 7 (11th March 2019) - May, M.; Brown, D. R.
Abstract : This report documents the International Committee on Systematics of Prokaryotes Subcommittee on the taxonomy of Mollicutes by recording the minutes of the meeting, held 8 July 2018, Portsmouth, New Hampshire, USA.